2017
DOI: 10.1002/ase.1759
|View full text |Cite
|
Sign up to set email alerts
|

Impact and educational outcomes of a small group self‐directed teaching strategy in a clinical neuroscience curriculum

Abstract: The complexity of the material being taught in clinical neuroscience within the medical school curriculum requires creative pedagogies to teach medical students effectively. Many clinical teaching strategies have been developed and are well described to address these challenges. However, only a few have been evaluated to determine their impact on the performance of students studying clinical neuroscience. Interactive, 2-hour, self-directed small-group interactive clinical case-based learning sessions were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…The studies identified in this review demonstrate that the teaching methods utilized, which aligned with the UDL framework, benefit the learning experience of medical, dental and OT students. These range from improved performance (Pratten et al, 2014; Manyama et al, 2016; Guimarães et al, 2019; Oakes et al, 2019; Lee et al, 2020; Mogali et al, 2020; Rao Bhagavathula et al, 2022) and understanding (Jaffar, 2012; Bergman et al, 2013b; Murphy et al, 2014; Nathaniel et al, 2018; Hoffmann et al, 2019) to enhanced participation (Inuwa et al, 2012; Pratten et al, 2014; Park & Howell, 2015) and confidence (Anyanwu, 2013; Manyama et al, 2016; Dua et al, 2021). The improvements and enhancements in teaching and learning reported in the selected studies can be attributed to the incorporation of technology, gamification, team‐based activities, peer‐assisted learning, an emphasis on the relevance of anatomy or the creation of a tailored anatomy learning environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies identified in this review demonstrate that the teaching methods utilized, which aligned with the UDL framework, benefit the learning experience of medical, dental and OT students. These range from improved performance (Pratten et al, 2014; Manyama et al, 2016; Guimarães et al, 2019; Oakes et al, 2019; Lee et al, 2020; Mogali et al, 2020; Rao Bhagavathula et al, 2022) and understanding (Jaffar, 2012; Bergman et al, 2013b; Murphy et al, 2014; Nathaniel et al, 2018; Hoffmann et al, 2019) to enhanced participation (Inuwa et al, 2012; Pratten et al, 2014; Park & Howell, 2015) and confidence (Anyanwu, 2013; Manyama et al, 2016; Dua et al, 2021). The improvements and enhancements in teaching and learning reported in the selected studies can be attributed to the incorporation of technology, gamification, team‐based activities, peer‐assisted learning, an emphasis on the relevance of anatomy or the creation of a tailored anatomy learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, there is scant research on how students enrolled in allied health programs are taught anatomy. For example, clinical therapy programs are considered new and young (Paden, 1970;Quiroga, 1995;Donnelly et al, 2013) when compared to the a Studies in which themes appear: A, (Abdullah et al, 2020); B, (Anyanwu, 2013); C, (Bacro et al, 2013);D, (Ben Awadh et al, 2022); E, (Bergman et al, 2013b); F, (Dua et al, 2021); G, (Felszeghy et al, 2019); H, (Gnanasegaram et al, 2020); I, (Golenhofen et al, 2020); J, (Guimarães et al, 2019); K, (Hoffmann et al, 2019); L, (Hu et al, 2016); M, (Inuwa et al, 2012); N, (Jaffar, 2012); O, (Kranz et al, 2017); P, (Lee et al, 2020); Q, (Lorenzo-Alvarez et al, 2020); R, (Ma et al, 2016); S, (Manyama et al, 2016); T, (McBride & Drake, 2015); U, (McCluskey et al, 2015); V, (Mogali et al, 2019); W, (Mogali et al, 2020); X, (Murphy et al, 2014); Y, (Nathaniel et al, 2018); Z, (Oakes et al, 2019); AA, (Ocak & Topal, 2015); AB, (Park & Howell, 2015); AC, (Pillay et al, 2019); AD, (Pratten et al, 2014); AE, (Rao Bhagavathula et al, 2022); AF, (Rezende et al, 2020); AG, (Yohannan et al, 2022).…”
Section: Universal Design For Learning In Third Level Anatomy Educationmentioning
confidence: 99%
“…Nathaniel et al .,[ 9 ] in a self-directed clinical case learning (SDCL) module followed for neuroscience, opine that it inspired students to set higher standards for themselves as the interactive sessions provide the platform to ask themselves incisive questions, to identify their biases and empowering them as intelligent contributors to their own learning processes. Our students’ attitude toward the intervention was also perceived positively; 86% of students responded to it as a highly recommended method of learning.…”
Section: Discussionmentioning
confidence: 99%
“…The learning benefits of small groups have been widely described. It promotes clinical reasoning and skills for lifelong learning [20][21][22] . Other advantages are integrating students with the development of friendships, sharing ideas, dividing the workload, tutoring, and learning support from others, and communication skills.…”
Section: Medicina Universitariamentioning
confidence: 99%